Overcoming acquired resistance to anticancer therapy: focus on the PI3K/AKT/mTOR pathway - Burris, Howard A. (Cancer chemotherapy and pharmacology, 2013)
Background Most targeted anticancer therapies, as well as cytotoxic and radiation therapies, are encumbered by the development of secondary resistance by cancer cells. Resistance is a complex phenomenon involving multiple mechanisms, including activation of signaling pathways such as phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR). Novel strategies to overcome resistance by targeting these signaling pathways are being evaluated. Methods PubMed and key cancer congress abstracts were searched until July 2012 for preclinical and clinical data relating to the PI3K/AKT/mTOR pathway and anticancer treatment resistance, and use of PI3K/AKT/mTOR inhibitors in resistant cancer cell lines and patient populations. Results Activation of the PI3K/AKT/mTOR pathway is frequently implicated in resistance to anticancer therapies, including biologics, tyrosine kinase inhibitors, radiation, and cytotoxics. As such, inhibitors of the PI3K/AKT/mTOR pathway are being rapidly evaluated in preclinical models and in clinical studies to determine whether they can restore therapeutic sensitivity when given in combination. In breast cancer, non-small-cell lung cancer, and glioblastoma, we find compelling preclinical evidence to show that inhibitors of PI3K or mTOR can restore sensitivity in resistant cells. Although clinical evidence is less mature, a recent Phase III study with the mTORC1 inhibitor everolimus in patients with advanced breast cancer resistant to aromatase inhibition and several Phase I/II studies with PI3K inhibitors demonstrate proof-of-concept, warranting future clinical evaluation. Conclusion Current preclinical and clinical evidence suggest that inhibitors of the PI3K/AKT/mTOR pathway could have utility in combination with other anticancer therapies to circumvent resistance by cancer cells. Multiple clinical studies are ongoing.